Pituitary adenomas - my personal experience - R Jha (Society of Surgeons of Nepal, 2016)
Introduction: The pituitary gland is also called the master gland of the body and its tumours represent 10- 15% of all intracranial tumors, with an annual incidence of 0.2-2.8 cases per 100,000 persons.Most are benign adenomas arising from the anterior pituitary (adenohypophysis), and most commonly present due to hormonal effects(includes hyperprolactinomia,Cushings Syndrome, acromegaly..),mass effect, as an incidental finding or infrequently with pituitary apoplexy.